Implementasi Pembelajaran Berdiferensiasi dalam Perspektif Teori Belajar Humanistik pada Sekolah Dasar: Studi Literatur - Nugroho, Citra Maulidyah Rahmawati; Darmawan, Puguh (Universitas Negeri Malang, 2024)
Penerapan pembelajaran berdiferensiasi dalam perspektif teori belajar humanistik disarankan untuk diadopsi di Sekolah Dasar sebagai respons terhadap kompleksitas tantangan pendidikan di era 21. Pendekatan pembelajaran ini memiliki potensi untuk memfasilitasi pengembangan potensi dan kreativitas siswa secara lebih optimal, sambil menyediakan pengalaman pembelajaran yang disesuaikan dengan karakteristik, gaya belajar, dan tingkat kesiapan individu siswa. Tujuan artikel ini untuk menganalisis implementasi pembelajaran berdiferensiasi dalam perspektif teori belajar humanistik di Sekolah Dasar. Penelitian ini menggunakan metode studi literatur dari berbagai sumber artikel pada jurnal elektronik. Hasil penelitian menunjukkan bahwa implementasi pembelajaran berdiferensiasi dalam perspektif teori belajar humanistik di Sekolah Dasar berhasil meningkatkan kreativitas dan pencapaian belajar siswa. Hal ini menegaskan pentingnya pendekatan ini dalam mengakomodasi keberagaman siswa untuk mengoptimalkan potensi dan kreativitas siswa. Siswa dapat belajar sesuai dengan karakteristik dan gaya belajar masing-masing dengan guru sebagai fasilitator. Penerapan ini direkomendasikan di Sekolah Dasar untuk mendukung proses pembelajaran yang intensif sesuai dengan kemampuan belajar siswa, sambil memastikan fasilitas pembelajaran yang memadai. Kata kunci: pembelajaran berdiferensiasi, sekolah dasar, studi literatur, teori belajar humanistik Implementation of Differentiated Learning in the Perspective of Humanistic Learning Theory in Elementary Schools: Literature Review The implementation of differentiated learning within of humanistic learning theory is recommended to be adopted in elementary schools in response to the complexity of educational challenges in the 21st century. This approach to learning has the potential to facilitate the development of students' potential and creativity more optimally, while providing a learning experience tailored to the characteristics, learning styles, and readiness levels of individual students. The aim of this article is to analyze the implementation of differentiated learning within the humanistic learning theory in elementary schools. This research employs a literature review method from various sources of articles in electronic journals. This study identifies that the implementation of differentiated learning within the perspective of humanistic learning theory in elementary schools has successfully enhanced students' creativity and academic achievements. This underscores the significance of this approach in accommodating student diversity to maximize their potential and creativity. Students can learn according to their characteristics and learning styles, with educators serving as facilitators. This implementation is recommended in elementary schools to support an intensive learning process tailored to students' learning abilities, while ensuring adequate learning facilities. Keyword: differentiated learning, elementary school, humanistic learning theory, literature review